2009
DOI: 10.1074/jbc.m803205200
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-nonspecific Alkaline Phosphatase Is Required for the Calcification of Collagen in Serum

Abstract: Previous studies have shown that the type I collagen of tendon and demineralized bone both calcify rapidly in serum. The speed, collagen matrix-type specificity, and extent of the re-calcification of demineralized bone in serum suggest that the serum calcification activity identified in these studies may participate in normal biomineralization. Because of its presence in serum and its long history of association with the normal mineralization of the collagen matrix of bone, tissue-nonspecific alkaline phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…Inactivation of AP prevents serum collagen calcification. AP was furthermore reported to activate a serum nucleator of apatite crystal formation (6). In line with this, clinical studies have found serum AP to be associated with coronary artery calcification and all-cause mortality in patients with CKD and on hemodialysis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 48%
“…Inactivation of AP prevents serum collagen calcification. AP was furthermore reported to activate a serum nucleator of apatite crystal formation (6). In line with this, clinical studies have found serum AP to be associated with coronary artery calcification and all-cause mortality in patients with CKD and on hemodialysis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 48%
“…It has been shown that this local increase of Ca ++ concentration may inhibit Zn ++ binding, depending on the relative abundance of these two divalent ions (Rosenberg et al, 1998). The association among the in situ release of Zn ++ , mineral precipitation and in vitro load cycling on partially demineralised and infiltrated dentine is supported by the effect of compressive loads on the stimulation of the tissuenonspecific alkaline phosphatase (McAllister and Frangos 1999), a zinc-metalloenzyme that hydrolyzes a broad range of phosphate monoesters (Price et al, 2009;Posner et al, 1986). At high phosphate concentration, calcium pyrophosphate, calcium phosphate and unstable and non-crystalline amorphous complexes are formed (Cheng and Pritzker, 1983) (Figs 4J, 5J) around the collagen fibrils, keeping the alkaline phosphatase and other enzymes "fossilized" (Van Meerbeek et al, 2001), thus hindering the complete remineralisation.…”
Section: Resultsmentioning
confidence: 97%
“…This deficiency results in accumulation of extracellular pyrophosphate and causes the inhibition of skeletal and dental mineralization [80][81][82][83]. There are six different clinical forms of the disease, and they are divided according to the age of the patient and degree of severity.…”
Section: Resultsmentioning
confidence: 99%